100 Years of Thrombotic Thrombocytopenic Purpura: A Story of Death and Life - Lämmle, Bernhard; Vanhoorelbeke, Karen; Kremer Hovinga, Johanna A.; Knöbl, Paul (Hämostaseologie, 2024)
One hundred years ago, in 1924, the first description of a patient with a disease, now known as thrombotic thrombocytopenic purpura (TTP) was published by Dr. Eli Moschcowitz. In honor of this report, this article, written by distinguished specialists in TTP, reviews the increase in scientific knowledge on this disease during the last 100 years. It covers the scientific progress from plasma therapy, the first beneficial treatment for TTP, to the elucidation of the pathophysiology, the discovery of ADAMTS13, the development of assays and targeted therapies up to the modern treatment concepts, that improved the outcome of TTP from an incurable disease to a well understood and treatable disorder.
Keywords: thrombotic thrombocytopenic purpura; ADAMS/ADAMTS 13; management of disease